2019
DOI: 10.5539/ijel.v10n1p101
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Factors Affecting Reading and Reading Habits of Preschool Children

Abstract: In the developing world, reading habit, which is one of the first habits of traditional education, continues primarily in the family and then in kindergartens. In this research, factors such as family, environment, kindergarten and libraries are discussed in terms of acquiring reading habit in preschool period and evaluations are made about the effects of these factors on reading habit. In this study, the results of the research on the factors in the reading habit of Ishık Kindergarten students of Ronaki Hawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…Lastly, regarding the community environment; research has found that the home environment is associated with children's reading abilities, having more or fewer books to read, and opportunities for children to go to the library. Also, activities organized in children's libraries are effective at improving children's reading habits too (Niklas, Cohrssen, & Tayler, 2016;Celik, 2020). This study encountered several limitations.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Lastly, regarding the community environment; research has found that the home environment is associated with children's reading abilities, having more or fewer books to read, and opportunities for children to go to the library. Also, activities organized in children's libraries are effective at improving children's reading habits too (Niklas, Cohrssen, & Tayler, 2016;Celik, 2020). This study encountered several limitations.…”
Section: Discussionmentioning
confidence: 92%
“…Children should be encouraged and supported, by caregivers, in good reading behavior while they are very young. The caring style of parents affects the development of children, including language skills (Kleemans, Peeters, Segers, & Verhoeven, 2012;Celik, 2020). Caregivers have a big role in being good reading models and giving an insight into reading to children (Wambiri & Ndani, 2015;Niklas, Cohrssen, & Tayler, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite unprecedented developments in technology, reading is still regarded as the best source of knowledge. Many studies have thus been carried out on reading habits from multiple dimensions such as gender (Scales & Rhee, 2001;Synder, 1981), age (Fusco, 1986;Celik, 2019), socio-economic conditions (Le et al, 2019;Devarajan, 1989), and family background (Greaney, 1986;Baker et al, 1997;Yusof, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research was conducted by Bunyamin Celik, it was a study on the factors affecting reading ad reading habits of preschool children. It highlighted on reading habits from the environment and family for acquiring reading habits (Celik, 2020).Thus, the motivation, strategy, and problem are needed to be discussed for further research on reading. Another reading research-based community is about a study creating a cohesive community through shared reading (Harder et al, 2015).…”
Section: Introductionmentioning
confidence: 99%